A experiência dos usuários de uma unidade básica de saúde no município de Osasco durante pandemia do vírus SARS-CoV-2 - Pinheiro, Jessica Lemos (2020)
The Coronavirus has been known to science since 1960 and seven major viruses are known to exist. With the emergence of the new Coronavirus SARS-Cov-2, many challenges are being faced in health services, it is important to know, evaluate and measure the experience of patients, in order to build facilities to improve the quality of health services. Objective: The present study aims to answer the following guiding question: What factors contributed to the experience of the population that went to the basic health unit in the municipality of Osasco during the SARS-CoV-2 virus pandemic period? Methodology: This is a cross-sectional epidemiological study with descriptive analyzes. The present study was carried out in October 2020. Data collection was performed through a questionnaire referring to the population's experience when attending a basic health unit. It is worth mentioning that all participants signed the Free and Informed Consent Form. Results: 168 approaches were taken, however, 47 patients chose not to participate in the research and 21 users did not fit the inclusion criteria, totaling 100 respondents. Conclusion: The present study found relevant points for the clinical practice of health care and management in view of the organization of the unit and the offer of educational actions in health.